Tanggung Jawab Penyedia Jasa File Hosting Atas Pelanggaran Hak Cipta yang Dilakukan Pengguna - Ridwan, Annisa Syaufika Yustisia (Yayasan Pengembangan Hukum Bisnis, 2013)
File hosting is basically an online data storage service, however most of its user use this service to conduct copyright infringement. As the result, many copyright holders suffer losses in form of sales decline. This research discusses why file hosting service provider shall be liable for copyright infringement conducted by its users and what is the legal test applied to attribute liability to file hosting service provider. This research is a juridical normative research which based on literary study. Legal material used in this research is primary legal materials including Indonesian Civil Code and related legislations. The findings indicates that: (1) File hosting provider shall be liable for the losses suffered by copyright holder by virtue of its legal obligation to respect exclusive rights of copyright holder and (2) Legal test applied to attribute liability to file hosting service provider is civil wrongdoing with regard of its elements which are conduct, unlawful characteristic, loss, mistake, and causal relationship between conduct and loss.